Species diversity of Mapania Aublet (Cyperaceae) from Malaysia - Zinnirah, Shabdin; Meekiong, Kalu (2012)
Twenty (20) species of Mapania were collected from Peninsular Malaysia and Borneo of which three, M. multiflora, M. sapuaniana and Mapania sp.1 are new records for Borneo. From published literature, Malaysia recorded a total 32 species. A field key is provided.